Cultural Diversity Analysis of Visual Content in the Indonesian Textbook: My Next Words for Elementary School Grade 1 - Febriana, Ridha Alya; Husaini, Nurfadillah; Rohim, Abdul (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The aim of this research is to analyze visual content that elevates Indonesian culture from the book